(untitled) (Sociología y tecnociencia, 2021)
Emerged in Wuhan China around Decembre 2019, the Covid-19 pandemic has spread allover the world and Indonesia is not an exception. By taking the case study on the West Kalimantan-Sarawak border area from April-June 2020, the main purpose of this study was to analyze the reality of the pandemic Covid-19 handling in the border area. Further, the paper has explored the causes of the small spread of Covid-19 in these border areas. Qualitative research methods were used in this research. Face to face interviews were conducted to collect qualitative data from the stakeholders. Second, documentation was used to obtain demographic, theoretical, and contextual data. This research reveals that in comparison with Pontianak, capital of West Kalimantan Province, the spread of Covid-19 in the border area was actually less. This phenomenon occurred because of the awareness and knowledge of the people in the border area. The information dissemination about Covid-19 and health protocols shared by the local government were augmented by local wisdom, mass organizations and religions which abetted to control the spread of pandemic.